Selection of Appropriate Quantum-Chemical Model for Calculations of Properties of Chromium Group Complexes via DFT - A.I. Kuramshin; M.V. Zimaliev; E.V. Kolpakova; V.I. Galkin (Учёные записки Казанского университета: Серия Естественные науки, 2016)
The selection of a pair of functional/basis for the most adequate quantum-chemical determination of the geometric and electronic properties of chromium group metal complexes with polydent heterocyclic ligands has been carried out. When selecting a suitable model, such parameters as allowable accuracy and acceptable time of calculation have been taken into account. It has been found that the accuracy of calculations depends on the number of basis functions in-volved in the calculation model – the error tends to decrease with the increase in their number. The ac-curacy of calculations also increases with introduction of the polarized orbitals 2d2p and 3df3pd in the quantum-chemical model and the diffuse orbitals p, pp, ppp in the basis, respectively. The results obtained by using non-hybrid functionals with large basis functions are comparable to the calculations performed in less time with the help of hybrid functionals. The optimal ratio for the accuracy of calculation results compared to the time for study of the coordi-nation compounds can be achieved by using the PBE0 hybrid functional and TZVPP basis functions.